Personal Tool for Protection on the Net - Yasir Ali Mahmood (International Journal Of Electrical Engineering and Inteligent Computing, 2024)
Every time a computer device connects to the Internet it is at risk. Data theft is one of the threats facing computers when they connect to the Internet. For a computer to connect to the Internet, it needs an IP address and a port address to send and receive data. When the data reaches the computer via a port, it needs to reach the process that requested this information, which is linked to that port. A process does all the internet connections by the compute. These processes need an approach to send and receive information, which is the ports themselves. The attacker uses this port to make a connection to the victim's computer to steal information. In such situations, support is crucially needed to prevent these attacks from affecting our system. This work develops a personal tool for helping users to protect themselves from external attacks. The proposed tool monitors the open ports and shows all the information about the processes that are used. The proposed tool can close the open port, kill the process associated with it, and delete the process. When closing this port, the attacker cannot have access to the victim's computer. The findings show that the proposed tool is highly efficient when it comes to computer protection. The experimental results also demonstrate that the features of the tool can be tuned to fit users’ interest.